2013
DOI: 10.1007/s10803-013-1925-5
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Attention Orienting in Young Children with Autism

Abstract: We examined the impact of simultaneous bottom-up visual influences and meaningful social stimuli on attention orienting in young children with autism spectrum disorders (ASDs). Relative to typically-developing age and sex matched participants, children with ASDs were more influenced by bottom-up visual scene information regardless of whether social stimuli and bottom-up scene properties were congruent or competing. This initial reliance on bottom-up strategies correlated with severity of social impairment as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 38 publications
5
58
0
Order By: Relevance
“…First, static images were chosen to increase our ability to exert control over low-level properties of the social and nonsocial stimulus pairs (e.g., visual angle, luminance, contrast, intensity, and orientation). Previous studies have found that individuals with ASD may process visual information differently from their typically developing peers, including superior performance on visual detail-oriented tasks (Plaisted et al, 1998; O'Riordan and Plaisted, 2001; O'Riordan et al, 2001; O'riordan, 2004; Mottron et al, 2006; Kemner et al, 2008) and attention that is differentially driven by low-level stimulus properties relative to typically developing peers (Amso et al, 2014). Thus, matching our social and nonsocial stimuli on these features helps ensure that any stimulus-type difference in attention between groups is not simply a function of low-level processing advantage in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…First, static images were chosen to increase our ability to exert control over low-level properties of the social and nonsocial stimulus pairs (e.g., visual angle, luminance, contrast, intensity, and orientation). Previous studies have found that individuals with ASD may process visual information differently from their typically developing peers, including superior performance on visual detail-oriented tasks (Plaisted et al, 1998; O'Riordan and Plaisted, 2001; O'Riordan et al, 2001; O'riordan, 2004; Mottron et al, 2006; Kemner et al, 2008) and attention that is differentially driven by low-level stimulus properties relative to typically developing peers (Amso et al, 2014). Thus, matching our social and nonsocial stimuli on these features helps ensure that any stimulus-type difference in attention between groups is not simply a function of low-level processing advantage in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Booth and HappĂ© (2010) reported a range of central coherence in typically developing school-age children as well as variability in older children with ASD. It is possible that bottom-up attentional strategies and a focus on fine-grained details of the visual environment is a less efficient word learning strategy and therefore, children who focus attention on low-level detail in the environment learn fewer words (Amso et al 2014). Although this hypothesis requires further investigation, some children with ASD may also show this type of processing for other aspects of their environment such as acoustic details of speech input (JĂ€rvinen-Pasley et al 2008), which would negatively affect language learning more generally.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been reported that children with ASD utilize bottom-up attention strategies to a greater extent than their peers when processing visual information, and this tendency has been found to correlate with their receptive language abilities and autism severity (Amso et al 2014). Using an eye-tracking paradigm, Amso et al (2014) found that preschool children with ASD relative to age-matched controls looked more at visually salient image regions regardless of the salience of the social content of the image. These investigators speculated that reliance on bottom-up attention strategies negatively impacts language and social development in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent evidence in individuals with ASD supports this possibility. In a study using eye-fixations as an index of attention orienting during complex naturalistic scenes, individuals with ASD fixated on social stimuli (faces, person) as much as controls, but differed qualitatively in visual attention orienting: adolescents with ASD were delayed in fixating on salient features (heads) (Freeth et al 2011) and children with ASD relied on bottom-up visual saliency when orienting to social stimuli to a greater extent than controls, which predicted social and communicative symptoms (Amso et al 2014). These findings support the view that atypical early-maturing visual attention processes contribute to social dysfunction in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Such bottom-up visual processing enhancement may lead to an over-reliance on visual saliency in attention orienting in ASD. How such enhancement may lead to the development of ASD symptoms has been speculated upon; increased attention to visual salience may decrease attention to social stimuli early in life, leading to diminished abilities to learn social constructs (Amso et al 2014; Joseph et al 2009). In addition, increased attention to visual salience may lead to a more general predisposition to focused attention in ASD, which may contribute to RRBI (Blaser et al 2014).…”
Section: Introductionmentioning
confidence: 99%